INFLUENCE OF POST-USAGE USEFULNESS, SELF-EFFICACY AND SATISFACTION TOWARDS CONTINUANCE INTENTION OF T-CASH - Juvelin, Laurenzia; Wulani, Fenika; Amrullah, Andi Anugerah (RIMA - Research In Management and Accounting, 2018)
In this era, digitalization becomes the trend on which everything goes digital and this includes paying through application. The users’ intention to continue using the application is very important. Based on the extended model of information technology continuance, the factors that influence the application continuance intention are post-usage usefulness, self-efficacy and satisfaction. This research aimed to analyze the influence of Post-Usage Usefulness, Self-Efficacy and Satisfaction Towards the Application Continuance Intention of T-Cash. This research is a causal study and uses a non-probability purposive sampling technique. The total number of respondents is 150 respondents who have T-Cash application and had experiences in using T-Cash application for payment in the last three months. The data were processed and analyzed by using Structural Equation Modeling technique through LISREL software. This research proved that Post-Usage Usefulness has a significant positive effect on the Application Continuance Intention and Satisfaction, Self-Efficacy has a significant positive effect on the Application Continuance Intention and Satisfaction, and Satisfaction has a significant positive effect on the Application Continuance Intention. The suggestions for T-Cash are to add more features that are beneficial for making payments faster, designing an easy and interactive user interface, and providing users with easy to follow instructions.